ENGLISH LEARNING ASSISTANCE USING INTERACTIVE MEDIA FOR CHILDREN IN ORGANIZATIONS IN WAJO DISTRICT - Satriani Satriani; Syahrun Adzim (Jurnal Abdimas Indonesia, 2021)
The Lecturer Team of the IAI As'Adiyah Tadris English Study Program provided assistance in studying English utilizing interactive media at the Wajo Regency Orphanage. The goal of this activity is to increase participants' enthusiasm in learning English by making it more appealing to them. It is intended that through utilizing interactive media, participants would be able to increase their ability to accurately use English terminology. Scrabble is the interactive medium utilized to provide this aid. This activity's data gathering comprises the following: (1) performance test questions to determine the number of participants who have mastered the vocabulary; the test is completed separately by each participant and presented at the conclusion of the learning material. (2) field notes, which involve documenting the English learning process and photographing activities both before and during the action. Based on the mentoring activities that have been completed, it can be concluded that the participants' attitudes have shifted from being less active, unenthusiastic, and less involved to being more active, enthusiastic, and willing to collaborate collaboratively during the mentoring activity, resulting in an increase in the participants' English vocabulary mastery skills.